Intestinal obstruction due to idiopathic mesenteric phlebosclerosis colitis: A case report - Shan, Jiaqi; Chen, Fangci; Yu, Panpan (Frontiers in Surgery, 2022)
Introduction Idiopathic mesenteric phlebosclerosis colitis (IMP) is a rare condition that impairs colonic venous blood return owing to mesenteric venous sclerosis and fibrosis. At present, many studies have suggested that long-term intake of Chinese herbal medicines is associated with its pathogenesis. IMP has no characteristic clinical manifestations, and most patients with IMP present with acute intestinal obstruction. As a rare disease, the etiology, pathogenesis, pathophysiology, and treatment of IMP are being explored and studied. Case Description A 60-year-old Chinese male patient with IMP was admitted to our hospital for acute intestinal obstruction, received subtotal colectomy and ileostomy after 10 days of ineffective conservative treatment, and was discharged after postoperative supportive treatment for 1 month. Conclusion There are many causes of intestinal obstruction, and we report a relatively rare one. After failure of conservative treatment, it is necessary to surgically resect part of the diseased bowel.